PILU MEMBIRU MUSICAL FORM ANALYSIS BY KUNTO AJI - Bazir, Rizkyatul; Hidayat, Robby; Pristiati, Tutut (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2022)
Musical form is the composition of music in a composition of motifs, themes, and phrases. Musical forms according to the number of sentences is divided into three types, namely one-part musical form, two-part musical form, and three-part musical form. This study aims to describe the musical form of the song "Pilu Membiru" by Kunto Aji. This research uses a qualitative descriptive research method. The data in the research were obtained using observation, interviews, and documentation by testing the validity of the data using triangulation. The results of this research indicate that the song "Pilu Membiru" by Kunto Aji has a complex three-part musical form. In the A complex section, there are 2 main themes and 1 transition theme. In part B complex there are 2 main themes with new themes that are played over and over again. Part C complex is a series of parts A complex and is played with increased dynamics to emphasize the part of the song. The complex three-part form of the song "Pilu Membiru" can be written in the musical form Ak (A, AI, B, BI, C ) - Bk (AII, D, D, D, D, D, D) - Ck (B, BI, C).The complex three-part form of the song "Pilu Membiru" can be written in the musical form Ak (A, AI, B, BI, C ) - Bk (AII, D, D, D, D, D, D) - Ck (B, BI, C).